A Digital Technology-Based Creative SME Development Model - Susano, Adhi (Edusight International Journal of Multidisciplinary Studies, 2025)
This research examines development models for creative micro, small and medium enterprises (MSMEs) through digital technology implementation. Data shows Indonesian MSMEs reach 65 million units contributing 61% to national GDP. The research employs qualitative approach with literature analysis and case studies of creative MSME practitioners. The developed model includes digital platform adoption, technology literacy development, and cloud-based business management system integration. Results indicate digital transformation increases market reach by 300% and operational efficiency by 45%. This model integrates information technology components, digital marketing, and digital financial management. Model implementation requires infrastructure support, human resource training, and capital access. The resulting model provides practical framework for creative MSMEs to adopt digital technology gradually and measurably